HUBUNGAN ANTARA FAKTOR PEMBENTUK BUDAYA KERJA K3 DENGAN PERILAKU SELAMAT PADA PEKERJA PROYEK PEMBANGUNAN APARTEMEN X TAHUN 2022 - Tasya Khaerunisa Putri (2022)
According to the International Labor Organization (ILO) in 2018, the rate of work accidents and various threats to occupational safety and health (K3) in Indonesia is still quite high. Based on work accident data in the project area, there were several work accidents for the period May 2021-January 2022. Therefore, the researchers conducted research on the factors that form a work safety culture related to safe behavior. The research method used is quantitative research with a cross-sectional study design and the sample used is 92 workers. The results showed as many as 92.3% of workers who carried out safe behavior actions. The results of the analysis obtained age variables (p-value = 0.024), years of service (p-value = 0.183), most recent education (p-value = 0.000), management commitment (p-value = 0.0200), regulations and procedures ( p-value = 0.822), worker communication (p-value = 0.083), employee involvement (p-value = 0.804), worker competence (p-value = 0.637), and work environment (p-value = 0.000). Variables that have a significant relationship with safe behavior are management commitment, rules and procedures and work environment. Companies need to increase worker participation in OHS activities in the project so as to increase worker competencies which have an impact on the quality of worker safety behavior. Suggestions that can be given are improving the quality of PPE for workers who are damaged, providing training related to accident prevention, reinforcing sanctions for workers who violate the rules, motivating workers to behave safely by giving rewards, ensuring the work environment in the project area is hazard free. Keywords : work accident, construction worker, factors forming a work safety culture